Social influence and cognitive instrumental factors as facilitators of perceived usefulness of electronic resources among library personnel in private universities in South-west, Nigeria. Issue 8 (27th October 2017) - Izuagbe, Roland; Popoola, Sunday Olanrewaju
Abstract : Purpose: The study examined the applicability of TAM2 theoretical constructs of social influence and cognitive instrumental factors vis-à-vis the facilitation of perceived usefulness of electronic resources among library personnel in private universities in South-west Nigeria. Design/Methodology/Approach: Descriptive research design of correlational type alongside the single-stage random sampling technique were used to select 212 respondents from a population size of 259 library personnel across the 21 private universities in South-west Nigeria. The instrument used to elicit data was the questionnaire. Of the 212 copies of the questionnaire administered, 181 (85.4 per cent) were found valid for analysis. Findings: Social influence and cognitive instrumental factors significantly had relationship with and facilitated perceived usefulness of electronic resources. Similarly, the study revealed that cognitive instrumental factors are stronger facilitators of perceived usefulness of electronic resources than social influence factors among library personnel in private universities in South-west, Nigeria. Practical implications: Implementation of electronic resources without ascertaining library personnel usefulness perception leads to resource underutilisation and wastage. Management of private university libraries should, therefore, take into cognisance the usefulness perception of library personnel before the implementation of electronic resources for optimum utilisation. Originality/value: There is no known research endeavour within the Nigerian context that examined perceived usefulness of electronic resources among library personnel in the private university domain, using the additional theoretical constructs of TAM2 as our research model suggests. This study is, therefore, a pioneering effort towards ascertaining library personnel's perceived usefulness of electronic resources prior acceptance and use in private university libraries.